Influence of Tattoo Ink on Hepatitis C Virus Infectiousness. (13th February 2019) - Behrendt, Patrick; Brüning, Janina; Todt, Daniel; Steinmann, Eike
Abstract: Hepatitis C virus (HCV) is a blood-borne virus and is most frequently transmitted through large or repeated direct percutaneous exposures to infected blood. The 2 most common exposures associated with transmission of HCV are blood transfusion and intravenous drug abuse. The association between HCV transmission and other suspected risk factors such as tattooing is more controversial. Although HCV can survive for days to weeks in suspension or on inanimate surfaces, its stability in tattooing supplies remains elusive. Here, we analyzed the influence of tattoo ink on HCV infectiousness.